2005
DOI: 10.1542/peds.2004-1970
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Evaluation in Children: Application to the CHARGE Syndrome

Abstract: ABSTRACT. Objective. To find an efficient tool for testing olfactory function in children and use it to investigate a group of children with CHARGE (coloboma, congenital heart disease, choanal atresia, mental and growth retardation, genital anomalies, and ear malformations and hearing loss) syndrome.Methods. We adapted for children an olfaction test that had just been validated in an adult French population and investigated a control group of 25 healthy children aged 6 to 13 years. We then tested the olfactory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 45 publications
1
62
0
Order By: Relevance
“…Documentation of cChd7 in the olfactory placode may shed light on the pathogenesis of genital anomalies in CHARGE syndrome. Chalouhi et al (2005) recently demonstrated that CHARGE syndrome patients fulfill the criteria for Kallmann syndrome, which combines hypogonadotropic hypogonadism with various degrees of deficiency in the sense of smell as a result of olfactory bulb aplasia or hypoplasia. Because hypogonadism in Kallmann syndrome results from the failed embryonic migration of GnRH-synthesizing neurons along the olfactory nerve pathway (Schwanzel-Fukuda et al, 1989), they suggested that hypogonadotropic hypogonadism in CHARGE syndrome may result from the same embryonic defect (Chalouhi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Documentation of cChd7 in the olfactory placode may shed light on the pathogenesis of genital anomalies in CHARGE syndrome. Chalouhi et al (2005) recently demonstrated that CHARGE syndrome patients fulfill the criteria for Kallmann syndrome, which combines hypogonadotropic hypogonadism with various degrees of deficiency in the sense of smell as a result of olfactory bulb aplasia or hypoplasia. Because hypogonadism in Kallmann syndrome results from the failed embryonic migration of GnRH-synthesizing neurons along the olfactory nerve pathway (Schwanzel-Fukuda et al, 1989), they suggested that hypogonadotropic hypogonadism in CHARGE syndrome may result from the same embryonic defect (Chalouhi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…39 It was observed by MRI scan in 18/18 patients. 38 Anosmia has recently be found to be a common anomaly, 40 in relation with abnormal olfactory bulbs.…”
Section: Choanal Atresia and Other Ent Anomaliesmentioning
confidence: 99%
“…15 In the radiologic diagnostic methods, Chalouhi et al 11 reported that anomalies of the olfactory bulbs and tracts might be pathognomonic for CHARGE syndrome and should be included as a major criterion for the diagnosis of this syndrome; Blustajn et al 10 recently reported that these anomalies were the most prevalent features of CHARGE syndrome. The present study showed that basioccipital hypoplasia and basilar invagination are significantly prevalent in the syndrome.…”
Section: (ϫ35)mentioning
confidence: 99%
“…[10][11][12] We encountered a few children with severe hypoplasia of the basiocciput during a radiologic assessment of patients with CHARGE syndrome. Basiocciput hypoplasia results in shortening of the clivus and is always associated with basilar invagination.…”
mentioning
confidence: 99%